Essays in money and banking / edited by C.R. Whittlesey and J.S.G. Wilson - Whittlesey, C.R. (ed.); Wilson, J.S.G. (ed.) (Oxford, 1968)
RICHARD SIDNEY SAYERS has for many years been a leading authority on money and banking. In this vol ume, friends and colleagues (some of them former students) have joined together in a common enterprise to honour him on his sixtieth birthday. Professor Sayers's own wide range of interests is reflected in the variety of the contributions, but it is not without significance that the main emphasis should be on monetary and banking history, a field in which Professor Sayers has himself written with such distinction. Nor is it an accident that the essays should be drawn from both sides of the Atlantic. They are a tribute to the high pro fessional standing of the man and the esteem in which he is held at home and abroad.
Keywords: Economics